(untitled) (International Journal of Innovative Technologies in Economy, 2023)
At the modern stage of Georgia’s development, for the formation of a democratic legal state, the solution to the problem of strengthening and improving the system of control and balance between the bodies of various branches of the state government is becoming more and more important. The constitutional reform, which was implemented in Georgia in 2017-2018, also covered the mechanisms of parliamentary control. Accordingly, the Parliament adopted new functions, which additionally defined new levers in the direction of executive power control. Parliamentary control mechanisms have existed at the legislative level in Georgia since the 1990s. However, their implementation practices were very sparse and often inconsistent. The purpose of the research is to systematically and detailed analysis of the mechanism of parliamentary control in Georgia as an institution, its management mechanism, to reveal the main features and to study the characteristics. The empirical basis of the presented research is the practice of parliamentary control and acts replacing parliamentary control. The normative base for the implementation of the research is created by the valid laws and legal acts that regulate the issues of parliamentary control in Georgia. The research is based on quantitative and qualitative social research techniques, as well as analysis and statistical methods. All this helped us in proper analysis and study of collected primary and secondary scientific information and materials. This study was conducted between August 20 and December 20, 2022. According to the results of this research, in the presented study, the significance of the control of the legislative body of Georgia as a system is studied. The functioning system and mechanisms of parliamentary control management are described. The parliamentary control system is defined as the characteristics of a transparent system of public administration. The problems of effective functioning of parliamentary control as a management system in Georgia are shown and recommendations are given that will contribute to strengthening the efficiency of parliamentary control in Georgia. This research is important, because many countries, especially transitional democracies, face similar problems in terms of executive control, so the analysis of Georgia’s experience will be useful for transitional democracies as well.